2015
DOI: 10.1136/bmjopen-2014-007034
|View full text |Cite
|
Sign up to set email alerts
|

Traffic pollution at the home address and pregnancy outcomes in Stockholm, Sweden

Abstract: BackgroundFor the past two decades, several studies have reported associations between elevated levels of ambient air pollution and adverse pregnancy outcomes, although with varying conclusions.ObjectivesTo examine possible associations between the traffic pollution situation at the home address, for women who did not change address during pregnancy, and three types of pregnancy outcomes: spontaneous preterm delivery, children born small for gestational age (SGA) and pregnancy-induced hypertensive disorders.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 37 publications
1
21
1
1
Order By: Relevance
“…Both short and long-term traffic-related air pollution (TRAP) exposure has been associated with adverse health effects, particularly for vulnerable populations such as pregnant women and children (McConnell et al, 2015; Olsson et al, 2015). Children are more vulnerable to the effects of air pollution because they breathe more air per unit of body weight than adults (Arcus-Arth and Blaisdell, 2007) and spend more time outdoors (Bateson and Schwartz, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Both short and long-term traffic-related air pollution (TRAP) exposure has been associated with adverse health effects, particularly for vulnerable populations such as pregnant women and children (McConnell et al, 2015; Olsson et al, 2015). Children are more vulnerable to the effects of air pollution because they breathe more air per unit of body weight than adults (Arcus-Arth and Blaisdell, 2007) and spend more time outdoors (Bateson and Schwartz, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Nine studies were identified that evaluated associations between traffic-related NO2 or NOx exposures and preeclampsia or combined hypertensive disorders of pregnancy. The available evidence included five retrospective cohort studies from Spain ), Sweden (Olsson et al 2015), the United States ) and Australia ; three prospective cohort studies from Denmark ), Norway (Madsen et al 2018), and The Netherlands (van den Hooven et al 2011); and one casecontrol study from Sweden ). The number of participants in these studies ranged from 7,000 to more than 260,000 pregnant women and included between 100 and 17,000 cases.…”
Section: Discussionmentioning
confidence: 99%
“…The number of participants in these studies ranged from 7,000 to more than 260,000 pregnant women and included between 100 and 17,000 cases. All studies assessed traffic-related NO2 or NOx exposures using LUR models Madsen et al 2018; or air dispersion models Olsson et al 2015; , , and reported median (IQR) levels of NO2 and NOx. b Blood pressure case sample size reflects the number of women who had blood pressure measurements taken.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Un lien a été observé entre l'augmentation des concentrations en NO et NO 2 et l'apparition de l'un des symptômes de PE (hypertension artérielle) chez la femme enceinte (Olsson et al 2015). De plus, une augmentation de la concentration en oxydes d'azote dans l'air environnant la femme enceinte est associée à une réduction, chez le nouveau-né, de la concentration plasmatique en vitamine D, impliquée dans de nombreux processus cellulaires et métaboliques dont le métabolisme des os et du calcium (Baiz et al 2012).…”
Section: Pathologie Placentaireunclassified